PSR J1735–0243: A Pulsar with Three Cone Components Exhibiting Mode-changing Behavior - Xin Xu; Qijun Zhi; Jie Tian; Jiguang Lu; Peng Jiang; Dai Shi; Shijun Dang; Guojun Qiao (The Astrophysical Journal)
We have carried out a detailed analysis of PSR J1735−0243 with the Five-hundred-meter Aperture Spherical radio Telescope at 1250 MHz. We found that this pulsar shows obvious mode changing, with approximately 82% in the normal mode and approximately 18% in the abnormal mode. The two modes differ not only in their integrated pulse profiles but also in their polarization properties. Further analyses suggest that the emission from the normal mode may originate from a higher height than the abnormal mode. Additionally, we found that the radio emission beam consists of four emission components, including a core component and three cone components. The tertiary cone component, which has the highest emission height, is present in both emission modes. Finally, the results shown that the radio emission of PSR J1735−0243 may have been generated in the core gap region.